Factors Causing Hearing Disorders Due to Noise at PT X Jakarta Timur Bearing Production in 2020 - Lutfi Dwi Aristiani; Mugi Wahidin; Hendry Amirudin; Gisely Violenita (Green Publisher Indonesia, 2021)
Hearing disorder is a disease caused by noise in the world and in Indonesia. There are many factors that contribute to hearing loss. This study aims to determine the factors associated with hearing loss in PT X Jakarta Timur Bearing Production workers in 2020. This study uses a Case Control design. The study population was 207 workers consisting of 42 cases and convenience sampling 42 controls. The data collection method was carried out by using a questionnaire for the variable length of service (ordinal), age (ordinal) and the use of APT (ordinal), looking at employee attendance data for the length of exposure variable (ordinal) and looking at Medical Check Up data for 42 respondents with a total sampling technique for case respondents and 42 control respondents for the variable hearing loss (ordinal). This study consisted of independent variables, namely noise intensity, length of exposure, age, years of service, and use of ear protection equipment (APT). The results of the research from the Chi-Square statistical test show that the factors that have a relationship are the length of exposure (p = 0.025) and age p = (0.004) in the PT X Jakarta Timur Bearing Production workers 2020. While the factors that have no relationship are noise intensity (p = 1,000), years of service (p = 0.602), and use of APT (0.169). It is recommended for companies to engineer overtime hours to reduce the length of exposure and carry out training for work-related illnesses, especially hearing loss, as a form of prevention of PAK. Companies can start mapping to relocate workers> 40 years old.